2020
DOI: 10.3390/horticulturae6040065
|View full text |Cite
|
Sign up to set email alerts
|

Stem Branching of Cycad Plants Informs Horticulture and Conservation Decisions

Abstract: The number of branches in male and female plants of Cycas micronesica K.D. Hill, Cycas edentata de Laub., Cycas wadei Merr., and Zamia encephalartoides D.W. Stev. were counted in Guam, Philippines, and Colombia, to confirm earlier reports that female plants develop fewer branches than males. Cycas plants produce determinate male strobili and indeterminate female strobili, but Zamia plants produce determinate strobili for both sexes. More than 80% of the female trees for each of the Cycas species were unbranche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The pachycaulous cycad stem is uniquely designed with a large primary thickening meristem and very few branches [ 64 ]. In fact, more than half of Guam’s female C. micronesica trees are unbranched [ 65 ]. Stem height growth is relatively slow, averaging about 3 cm per year for Guam’s population [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pachycaulous cycad stem is uniquely designed with a large primary thickening meristem and very few branches [ 64 ]. In fact, more than half of Guam’s female C. micronesica trees are unbranched [ 65 ]. Stem height growth is relatively slow, averaging about 3 cm per year for Guam’s population [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of non-native insect herbivores on a native host tree are not restricted to mortality. We have reported that chronic herbivory of C. micronesica by these non-native insects has caused reductions in stem carbon dioxide efflux [ 90 ], has selectively killed more unbranched trees than branched trees to indicate more female trees have died than male trees [ 65 ], has compromised the success rate of adventitious root formation on stem cuttings [ 91 ], and has reduced the rate of tree height growth [ 66 ]. Additionally, we have reported substantial changes in leaf litter chemistry following herbivory in a manner that predicts increased decomposition rates [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conservation of unique plant species has significant ecological and horticultural implications. Marler and Calonje [14] observed that male Cycas and Zamia plants produced more branches than female plants, and cycad species with determinate female strobili produced more branches on female plants than species with indeterminate female strobili. Horticultural and conservation decisions may be improved with this sexual dimorphism knowledge.…”
Section: Expanding Our Knowledge Of Unique and Underutilized Species Is Key To Their Conservation And Horticultural Usementioning
confidence: 99%
“…Branching behaviors of cycad trees are unique, and many female trees remain unbranched for life. In contrast, most male trees exhibit several points of dichotomous branching [63]. The pre-invasion Guam populations of C. micronesica were comprised mostly of unbranched trees, but after 15 years of A. yasumatsui damage most of the remaining live trees contained three or more branches.…”
Section: Individual Plant Responsesmentioning
confidence: 99%